End-to-end 5G testbed characterisation and improvements at 60GHz - Sismeiro, Luís Eduardo de Sousa (2018)
Wireless communications for the next mobile generation, the 5G, are set to increase both throughput and reliability than what is currently seen in mobile systems. These are set to be able to cope with the increase in mobile subscribers that is bound to occur in the next years and with the increasing demand in data rates and lower latency for immediate access to high-volume data. Therefore, this dissertation describes a characterization of a full end-to-end 5G testbed at 60 GHz capable of transmitting up to 1 Gbps. This characterization will evaluate the current state of the art of 60 GHz commercial front-end devices and compare it to a custom solution. This characterization evaluates both performance and Radio Frequency (RF) impairments. Furthermore, the baseband system is also evaluated in performance and signal impairments. To conclude the performance evaluation of the commercial device, a real-world scenario was drawn and tested where this emulates an Augmented Reality (AR) wireless device and evaluates the feasibility of such system on a classroom environment. To scale this work and improve signal reliability, a Multiple-Input Multiple-Output (MIMO) Alamouti transmission and receiver diversity block code on System Generator was also devised and simulated .